PELAKSANAAN KESEPAKATAN BERSAMA ANTARA PT WIRA KARYA PRAMITRA DENGAN FEDERASI SERIKAT PEKERJA TRANSPORT INDONESIA/KONFEDERASI SERIKAT PEKERJA SELURUH INDONESIA KABUPATEN KAMPAR DALAM BONGKAR MUAT TANDAN BUAH SEGAR KELAPA SAWIT - Lamtiar Lamtiar; Evi Deliana; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
This study discusses the implementation of a joint agreement between PT. Wira Karya Pramitra with Labor Unions in Kampar District. The choice of this theme is motivated by the fact that PT Wira Karya Pramitra and the Kampar Regency Labor Union have not yet carried out their roles as agreed upon as parties to the agreement. In the implementation of the agreement not yet in accordance with Article 1313 Regarding the Agreement Born from the Contract or Agreement. The problem that occurs is the payment of loading and unloading of fresh fruit bunches paid by the fruit suppliers namely oil palm farmers so that the farmers object to the agreement and write to the Kampar Regency Trade Unions to be able to reduce the price of loading and unloading of fresh fruit bunches of oil palm. Whereas in the mutual agreement letter that was agreed between PT. Wira Karya Pramitra with the Kampar Regency Labor Union agreed that the loading and unloading wages of fresh fruit bunches were paid by PT. Wira Karya Pramitra in accordance with the provisions of article V paragraph 9. The purpose of writing this thesis, namely; First, to find out how the implementation of the joint agreement carried out by PT Wira Karya Pramitra with trade unions, Second, To know the obstacles faced in implementing the collective agreement agreement made by PT Wira Karya Pramitra with trade unions.From the results of the research there is a main problem. First, the union as a representative of the extension of the loading and unloading workers and oil palm farmers with PT. Wira Karya Pramitra, Second, The obstacles faced by the Labor Unions of Kampar Regency and PT Wira Karya Pramitra are the low quality of human resources, lack of communication, as well as obstacles from employers and the government. Author Suggestions, First, the parties, namely PT. Wira Karya Pramitra and Trade Unions in order to be able to carry out collective agreements well and pay more attention to the welfare of the Loading Unloaders as well as the oil palm farmers. Secondly, PT Wira Karya Pramitra must comply with the collective work agreement or agreed collective agreement.Keywords: Agreement - Mutual Agreement - Contract